Daikenchuto, a Japanese herbal medicine, ameliorates experimental colitis in a murine model by inducing secretory leukocyte protease inhibitor and modulating the gut microbiota - Ozaka, Sotaro; Sonoda, Akira; Kudo, Yoko; Ito, Kanako; Kamiyama, Naganori; Sachi, Nozomi; Chalalai, Thanyakorn; Kagoshima, Yomei; Soga, Yasuhiro; Ekronarongchai, Supanuch; Ariki, Shimpei; Mizukami, Kazuhiro; et al. (Frontiers in Immunology, 2024)
Background Inflammatory bowel disease (IBD) is a refractory inflammatory disorder of the intestine, which is probably triggered by dysfunction of the intestinal epithelial barrier. Secretory leukocyte protease inhibitor (SLPI) secreted by colon epithelial cells protects against intestinal inflammation by exerting anti-protease and anti-microbial activities. Daikenchuto (DKT) is one of the most commonly prescribed Japanese traditional herbal medicines for various digestive diseases. Although several animal studies have revealed that DKT exerts anti-inflammatory effects, its detailed molecular mechanism is unclear. This study aimed to clarify the anti-inflammatory mechanism of DKT using a murine colitis model, and to evaluate its potential as a therapeutic agent for IBD. Methods Experimental colitis was induced in wild-type (WT) mice and SLPI-deficient (KO) mice by dextran sulfate sodium (DSS) after oral administration of DKT. The resultant clinical symptoms, histological changes, and pro-inflammatory cytokine levels in the colon were assessed. Expression of SLPI in the colon was detected by Western blotting and immunohistochemistry. Composition of the gut microbiota was analyzed by 16S rRNA metagenome sequencing and intestinal metabolites were measured by gas chromatography-mass spectrometry analysis. Intestinal epithelial barrier function was assessed by oral administration of FITC-dextran and immunostaining of tight junction proteins (TJPs). Results Oral administration of DKT increased the number of butyrate-producing bacteria, such as Parabacteroides, Allobaculum, and Akkermansia, enhanced the levels of short-chain fatty acids, including butyrate, in the colon, induced SLPI expression, and ameliorated DSS-induced colitis in WT mice. We found that mouse colon carcinoma cell line treatment with either DKT or butyrate significantly enhanced the expression of SLPI. Moreover, supplementation of DKT protected the intestinal epithelial barrier with augmented expression of TJPs in WT mice, but not in KO mice. Finally, the composition of the gut microbiota was changed by DKT in WT mice, but not in KO mice, suggesting that DKT alters the colonic bacterial community in an SLPI-dependent manner. Conclusion These results indicate that DKT exerts anti-inflammatory effects on the intestinal epithelial barrier by SLPI induction, due, at least in part, to increased butyrate-producing bacteria and enhanced butyrate levels in the colon. These results provide insight into the mechanism of the therapeutic effects of DKT on IBD.